2013
DOI: 10.2320/matertrans.md201207
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Interfacial Shear Force during Ultrasonic Al Ribbon Bonding

Abstract: An Al ribbon was bonded to SiO 2 substrate with a 60 kHz ultrasonic wedge bonder. The shear force applied at the interface between the ribbon and the substrate was measured with a piezoelectric load-cell. Simultaneously, the vibration amplitude at the tip of bonding tool was monitored with a laser-Doppler vibrometer. It was suggested from experimental results that the maximum interfacial shear force was 6.4 times larger than the bonding force, i.e., the friction coefficient at the interface could be significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The detailed reasons for the local detachment can be further summarized as follows: (i) both large vibration amplitude and interfacial shear force in the initial stage, which were demonstrated by Ando et al, 23) (ii) too small bonded area at initial interface, which was unable to suppress or stop relative motion of Al ribbon even if the isolated adhesion was strong, (iii) enhanced shear effect of strong Cu on weak Al by some detectable peaks on Cu surface (Fig. 2), and (iv) lower shear strength of the weak Al base metal.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The detailed reasons for the local detachment can be further summarized as follows: (i) both large vibration amplitude and interfacial shear force in the initial stage, which were demonstrated by Ando et al, 23) (ii) too small bonded area at initial interface, which was unable to suppress or stop relative motion of Al ribbon even if the isolated adhesion was strong, (iii) enhanced shear effect of strong Cu on weak Al by some detectable peaks on Cu surface (Fig. 2), and (iv) lower shear strength of the weak Al base metal.…”
Section: Resultsmentioning
confidence: 97%
“…23) USW can be considered as a special friction welding process, in which the small amplitude (several micrometers) requires ultrahigh frequency to rapidly accumulate thermalmechanical effect on joining interface and then to achieve oxide film removal and intimate contact at interface. But the conditions of USW are quite different from general friction welding in clamping and driving modes, bonding pressure level, temperature and deformation and relative displacement (in tangential direction) levels at interface, leading to different interfacial microstructure feature and its forming mechanism.…”
Section: Usw Joint Formation Mechanismsmentioning
confidence: 99%
“…Al ribbon bonding is applied to power electronics packaging as well as to Al wire bonding [1,[6][7][8]. Various studies of solid state ultrasonic microjoining have been reported [1,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The dominant mechanism consists of friction slip, plastic deformation, frictional heating and interfacial reaction (interdiffusion) [9][10][11][12][13][14]22].…”
Section: Introductionmentioning
confidence: 99%
“…These mechanism elements influence each other; additionally, their contributions are changed by the bonding conditions (bonding force, F b , and ultrasonic power, P u ) [1,3,[9][10][11][12][13][16][17][18]. Frictional heating can soften materials when microjoining; however, the softening effect cannot be attributed to frictional heating alone [13,21]. The increase in frictional force (shear force) in a direction parallel to the bonding interface contributes to the softening effect [1,21,[23][24][25], as it is related to frictional slip and interfacial adhesion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation